LEARNING ENGLISH THROUGH REFLECTION: A NARRATIVE INQUIRY INTO HOW STUDENTS PERCEIVE AND CORRECT THEIR LINGUISTICS ERRORS - Raifa Naswa Khodijah; Lubis, Elfi Mawaddah; Dwita Lestari; Dian Fanny Sarahseti; Siti Ismahani (Linguistics and Literature Journal, 2025)
This study explores how Indonesian university students perceive and correct their linguistic errors through reflective learning, using narrative inquiry as the central methodological approach. While linguistic errors are commonly examined through structural or quantitative perspectives, less attention has been given to how learners themselves interpret these errors and construct meaning from them. Through in-depth narrative interviews and reflective journals, this research illuminates the emotional, cognitive, and experiential dimensions that shape students’ engagement with their mistakes. The findings reveal three major themes: the development of error awareness, the interplay between emotional responses and cognitive processing, and the adoption of reflective strategies such as self-monitoring, contrastive thinking, and contextual experimentation. These narratives demonstrate that reflection transforms errors from mere deviations into valuable learning resources that promote metacognitive growth, resilience, and autonomy. By highlighting the personal stories behind error correction, the study contributes to a more humanistic understanding of language learning and underscores the need for reflective pedagogy in higher education EFL contexts.Keywords: EFL learners, learner awareness, linguistic errors, metacognition, Narrative inquiry, reflective learning